Analisis Dugaan Strategi Korporasi dalam Menyamarkan Praktik Kepailitan melalui Skema Kebangkrutan Fiktif - Dea Kuni Fauziyah; Halimah Zahrah; Putri Ayuningtyas; Salsabila Fauziah; Tania Kirana Aprilia (Teewan Journal Solutions, 2025)
This research is motivated by the bankruptcy phenomenon of PT Sri Rejeki Isman Tbk (Sritex), one of the largest textile companies in Southeast Asia, which is considered not only a financial failure, but also reflects the potential for deviations in business ethics and corporate governance. The main problem in this study is to critically analyze the alleged strategy used by PT Sri Rejeki Isman Tbk (Sritex) in disguising corruption practices and financial irregularities through a fictitious bankruptcy scheme. The purpose of this study is to analyze in depth the alleged corporate strategy in disguising bankruptcy practices through a fictitious bankruptcy scheme, by making the case of PT Sritex as the main study. This study uses a qualitative-descriptive approach method by examining secondary data from court decisions, media coverage, and scientific articles to reveal patterns of misuse of legal instruments such as PKPU and bankruptcy status as a shield against legal accountability. The results of the study show strong indications of financial report manipulation, non-transparent collaboration between management and financial institutions, and weak implementation of Good Corporate Governance (GCG) principles. This highlights the urgency of corporate governance reform and supervision of financial institutions to prevent abuse of the legal system. This study recommends in-depth reform of the corporate oversight system, increased transparency of reporting, and stricter law enforcement, to prevent similar abuses in the future and strengthen the integrity of business ethics in Indonesia.